The improvising mind cognition and creativity in the musical moment - Berkowitz, Aaron, 1978- (Oxford : Oxford University Press, 2010)
The ability to improvise represents one of the highest levels of musical achievement. Yet what musical knowledge is required for improvisation? How does a musician learn to improvise? What are the neural correlates of improvised performance? These are some of the questions explored in this unique and fascinating work.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Improvisation (Music); Music -- Psychological aspects; Cognition